Family Relationships From Adolescence to Early Adulthood: Changes in the Family System Following Firstborns’ Leaving Home - Whiteman, Shawn D. (2011)
This study charted the course of parent-child and sibling relationships from early adolescence to early adulthood and examined how these relationships changed following firstborns’ departure from their parents’ home for the first time. Data were drawn from a 10-year longitudinal study of family relationships. Participants included mothers, fathers, and first- and second-born children from 184, White, working and middle class families. Multilevel models revealed declines in parent-child conflict, acceptance, and sibling negativity, and increases or U-shaped patterns in sibling and parent-child intimacy over time. Birth order X leaving home interactions revealed that firstborns’ leaving home related to changes in family relationship qualities for both first- and second-borns, with relationships improving for firstborns and no changes or declines in relationship quality for second-borns. Overall, the results highlight the inter-relatedness of family subsystems.